Simultaneous clavicular hook plate fixation in bilateral distal clavicle fractures (Neer type II): A case report - Akar, Bedrettin; Ugur, Fatih (Ovid Technologies (Wolters Kluwer Health), 2024)
Rationale: Bilateral distal clavicle fractures (BDCF) are exceedingly rare types of fractures. This study aimed to evaluate the surgical treatment under a single anesthesia for trauma-induced BDCF (Neer type II) through a case report. Patient concerns: The patient brought to the emergency department due to a motor vehicle accident exhibited severe pain, tenderness, swelling, and deformity in both shoulder regions upon physical examination. No significant pain or tenderness was detected in other areas of the body. There were also no signs of additional neurological deficits or vascular pathology in the extremities. Diagnoses: Radiographic examinations led to a diagnosis of BDCF (Neer type II). Interventions: Surgical intervention involved the simultaneous application of a neutral-angled hook plate to both clavicles via open reduction. Outcomes: Postoperative radiographs taken at the 12th week demonstrated complete healing in both fractures and no functional limitations in shoulder movements. Lessons: BDCF can compromise the stability of the shoulder girdle, necessitating surgical intervention with anatomical reduction and rigid fixation.
Keywords: Male; Adult; Fractures, Bone; Fracture Fixation, Internal; Accidents, Traffic; Humans; Clavicle; Bone Plates